High-temperature injection spectroscopy of deep traps in CdTe polycrystalline films - Opanasyuk, A.S.; Opanasyuk, N.N.; Tirkusova, N.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The paper provides the direct experimental method to determine the localized state energy distribution function for semiconducting solid materials based on space-charge-limited current-voltage characteristics. The current-voltage characteristics would be obtained under the random temperatures. The Tikhonov regularization method was used to solve the Fredholm 1st rank equation. The method developed in this research was used for the study of deep traps in CdTe polycrystalline films obtained in quasi-closed-tube on the conducting substrate. In the bend gap of the material, some traps were traced, which can be described by the close to Gaussian distribution parameters as well as by the parameter of energy disorder = 0.015-0.04 eV. The research shows that the trap concentration and depend on the physical and technological conditions of the obtained films, while the energy of the traps depends on the impurity-defective material structure.